2020
DOI: 10.1017/s1368980020002529
|View full text |Cite
|
Sign up to set email alerts
|

Physical function after dietary weight loss in overweight and obese adults with osteoarthritis: a systematic review and meta-analysis

Abstract: Objective: Osteoarthritis (OA) is associated with functional limitations that can impair mobility and reduce quality of life in affected individuals. Excess body weight in OA can exacerbate impaired physical function, highlighting the importance of weight management in this population. The aim of this systematic review was to compare the effects of different dietary interventions for weight loss on physical function in overweight and obese individuals with OA. Design: A comprehensive sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In addition, semaglutide, which had the greatest effect on weight loss within this analysis, resulted in the greatest improvement in IWQOL‐Lite physical function scores and one of the strongest effects on SF‐36 scores. Results of a 2020 study investigating the effects of a dietary intervention on physical function showed that meal replacement or very low‐energy diets were more effective than any other lifestyle programs for improving physical function 10 . Therefore, it is likely that improvements in self‐reported physical function are proportional to the amount of weight lost.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, semaglutide, which had the greatest effect on weight loss within this analysis, resulted in the greatest improvement in IWQOL‐Lite physical function scores and one of the strongest effects on SF‐36 scores. Results of a 2020 study investigating the effects of a dietary intervention on physical function showed that meal replacement or very low‐energy diets were more effective than any other lifestyle programs for improving physical function 10 . Therefore, it is likely that improvements in self‐reported physical function are proportional to the amount of weight lost.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in biomechanical loading resulting from weight loss can enhance an individual's ability to undertake everyday tasks of living with improved physical functioning. This is consistently observed particularly after dietary‐induced or surgically induced weight loss interventions 8–10 . Epidemiological research has also suggested a bi‐directional relationship between weight change and activity, where reduced body weight may contribute to increasing physical activity levels 11,12 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“… 116 It is possible that the improvements in mental well‐being seen at mid‐diet and potentially at post‐diet, may be—in part—a result of these biological shifts. 116 It is also important to note that physical quality of life (e.g., physical functioning) is likely to have improved across participants included in our meta‐analyses, 117 , 118 and that any improvements in physical quality of life may have had indirect effects on mental well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…While knee OA clinical guidelines recommend weight loss [ 14 , 15 ], they do not specify how best to do this or which dietary approach to use. There is evidence to show that very low calorie diets (VLCDs) involving meal replacements are more effective for inducing significant weight loss and improving physical function than diets that involve lifestyle counselling alone in people with knee OA [ 29 ]. Ketogenic VLCDs, whereby carbohydrate intake is additionally restricted (< 50-60 g per day), have also been demonstrated to be an effective and safe means of achieving rapid weight loss in the adult population with overweight and obesity [ 30 ] and lead to greater weight loss than low-fat diets in the short-term [ 31 ].…”
Section: Introductionmentioning
confidence: 99%